Withdrawal: Development of a robotic system for prostate interventional therapy. Issue 1 (22nd November 2021) - Unknown
ABSTRACT: Khalil, I. and Omisore, OM. (2021), Development of a robotic system for prostate interventional therapy. Int J Med Robot. Accepted Author Manuscript e2236. https://doi.org/10.1002/rcs.2236 . The above article from The International Journal of Medical Robotics and Computer Assisted Surgery, published online on 29‐Jan‐2021 on Wiley Online Library (http://wileyonlinelibrary.com ) has been withdrawn to allow the authors to register a patent for prostate interventional therapy, by agreement between the Editor‐in‐Chief and John Wiley & Sons Ltd.